Dilated intecellular spaces of oesophageal epithelium among Malaysian with nonerosive reflux disease : an electron microscopic study - Norlinda binti Abd Rashid (Kulliyyah of Medicine, International Islamic University Malaysia, 2011)
Background: The dilatation of intercellular space (DIS) is identified as an early and sensitive morphological marker of oesophageal damage. Objective: The main aim of this study was to evaluate intercellular space dilatation DIS of oesophageal epithelium and to find out the association between clinical symptoms and DIS among Malaysian with non erosive reflux disease (NERD) in Hospital Tengku Ampuan Afzan (HTAA) Kuantan, Pahang, Malaysia. Methodology: The study group included 8 patients with reflux symptoms, normal mucosa on endoscopy and positive 24-hour pH monitoring( NERD) and 5 normal controls. Specimens were routinely processed for transmission electron microscopy (TEM) & surface electron microscopy (SEM). The intercellular spaces between the most superficially located esophageal epithelial cells and prickle cell layers were viewed by SEM and TEM respectively. The widths of intercellular spaces were determined by transmission electron microscopy (TEM). Results: Morphometric analysis on transmission electron microscopy microphotographs showed mean intercellular space diameter values of NERD patient was significantly ( two times) higher than those in normal controls (p<0.001). The cut-off value of > 0.93 μm is considered as dilated. There was significant different between DIS and heartburn but not with acid regurgitation. SEM studies showed that no dilatation of intercellular space was found only in 2 (40%) subjects of control group. Mild dilatation in some areas (Grade 2) was found in 3 (60%) of controls and 1 (12.5%) of NERD subjects. 7 (87.5%) NERD subjects showed Grade 3 oeosphageal surface dilatation. There was significant different between DIS of prickle layer cells and most superficially located oesophageal cells (P=0.007), and there was no association between clinical outcome with DIS of surface epithelium cells. Conclusion: We documented that DIS at prickle layer can be as a marker of oesophageal damage but not at the superficially located surface epithelial cells. Our cut-off score for DIS in Malaysian with NERD was >0.93 μm. If this result can be confirmed in large series it may provide a useful diagnostic tool for NERD patients.